Comparison of Hemolysis Events and Hematocrit Quality in Leucodepleted (In Line) and Leucodepleted (Bedsite) Clinical Transfusions - Frisca Novasari Saragih; Hendy Million; Masyitah Masyitah (CV. Inara, 2023)
Blood transfusions no longer provide all the blood components but only provide the necessary blood components. We aim to determine whether there is a comparison of hemolysis events and hematocrit quality in leucodepleted (In Line) and leucodepleted (Bedsite) clinical transfusions. This study was an analytic study with a cross-sectional design to compare hemolysis events and hematocrit quality in leucodepleted (In Line) and leucodepleted (Bedsite) clinical transfusions. We obtained sample data in this study divided into 2 groups, namely the group with leucodepleted in line and the group with leucodepleted bedsite inclusion and exclusion criteria of 58 samples.We found that the incidence of hemolysis after leucodepleted (in line) was 0% and leucodepleted (bedsite) was 0.02%, where the standard percentage of blood hemolysis was <0.8%, the hemolysis incident after the production of the two products was very small. While the hematocrit before and after leucodepleted decreased by 35.91% in leucodepleted (in line) and 33.33% in leucodepleted (bedsite). There is a comparison of the incidence of leucodepleted (In Line) and leucodepleted (Bedsite) hemolysis. Where the incidence of leucodepleted (in line) hemolysis is not found, so the leucodepleted (in line) blood component has good quality. There is a comparison of the quality of leucodepleted (In Line) and leucodepleted (Bedsite) hematocrit.